Execution of Diplomatic Law in International Relations and Foreign Policy of Nepal - Kunwar, Kalidas; Acharya, Abinav (KDCBAR Law Journal, 2025)
Diplomatic law is a branch of public international law that governs the conduct of diplomacy between the states. It primarily focuses on the rights, privileges, immunities and responsibilities of diplomatic agents, missions and consular staff. There are a few legal bases that support the conduct of diplomatic law through the Vienna Convention on Diplomatic Relations (1961), Vienna Convention on Consular Relations (1963) and Customary International Law. These conventions codify the standards for diplomatic relations, including establishment of diplomatic missions, immunities and privileges of diplomatic staff, inviolability of diplomatic premises, rules of conduct and limitations for the prosperity and sustainability of international relations. Nepal is a party to major international conventions governing diplomatic law: ratified the Vienna Convention of Diplomatic Relations (1961) and the Vienna convention on Consular (1963). These treaties have been incorporated into Nepalese legal practice through the Treaty Act, 1990 (2047 B.S) which gives precedence to international treaties over national law if there is a conflict. Thus, a state policy and international law provision in Nepal’s constitution (2015) promotes compliance with international law and norms. Diplomatic Code of Conduct 2011, monitor the norms and diplomatic conduct of the Nepalese diplomats. The objective of the research article is to analyze the Diplomatic law and its execution in Nepal in respect to international law and international relations and foreign policy. The research methodology is based on the doctrinal research method and the various data and information has been taken from the secondary data.